Subcapsular hematoma of liver - Fronzuti, Agustín; Armand Ugón, Alfredo; Carrera, Carlos; Perdomo, Roberto (Cirugía del Uruguay, 1978)
The authors study a case of broken liver subcapsular hematoma, with large hepatic invasive surface. It is worth pointing out the following aspects: a} usefulness of paracentesis as diagnostical procedure; b) advantage of employing transversal incisions which permit a wide approach to supramesocolic víscera; c) hemostasis of invasive surface through application of pediculate omentum when it is not possible to approximate the capsule; and d) the value of careful evolutive control of patient in a specialized centre.